RETRACTED: AnnexinA5 Might Suppress the Phenotype of Human Gastric Cancer Cells via ERK Pathway - Wang, Xiaojie; Dai, Yarui; Zhao, Yina; Li, Meichuan; Zhang, Jialu; Ci, Yunzhe; Wang, Huan; Li, Xin (Frontiers in Oncology, 2021)
Gastric cancer is one of the most fatal disease around the world. However, the mechanism of the development of gastric cancer is still not clarified. In addition, the anticancer drugs have cytotoxicity with different degrees. AnnexinA5, a member of annexin family, has great binding ability with the membrane phospholipid in a calcium dependent manner, is involved in the development of various cancers. To explore the influence of annexinA5 on human gastric cancer cells and whether it has the potential to be an auxiliary treatment to gastric cancer. In this study, the role of annexinA5 was detected from both the endogenous and the exogenous aspects on the gastric cancer cell lines MGC-803 and MKN-45. The cells were divided into a knockdown group in which RNA interference technique was used to suppress annexinA5 expression and a protein-supplementing group in which annexinA5 protein was added in the culture supernatant. After the suppression ratio of RNA interference was determined and the IC50 of annexinA5 protein was decided respectively, the cells proliferation was detected by MTT assay, colony formation assay and the expression of PCNA. FCM assay and PI staining methods were applied to test cell apoptosis and necrosis. To investigate whether ANXA5 influence cell metastasis, wound healing assay and transwell assay were employed. To further detect the mechanism of annexinA5 action, the signal pathway was examined with Western Blot method. When ANXA5 gene was knocked down, cell proliferation and metastasis were promoted while cell apoptosis was suppressed. On the other hand, after the annexinA5 protein was applied to the gastric cancer cells, cell proliferation and metastasis was inhibited while cell apoptosis and necrosis was promoted. AnnexinA5 played its role via ERK signal pathway.ANXA5 acted as tumor suppressor gene in the gastric cancer by suppressing ERK signal pathway and has the potentiality to be an auxiliary anticancer agent.